Konflik Sosial Tokoh Utama dalam Film Animasi Haikyuu!! Second Season (Kajian Sosiologi Sastra) - Niken Sekar Ayu Nurfajriyati; Ayu Putri Seruni (KIRYOKU, 2022)
Social conflict was defined as a natural social symptom that occurs in social life. Coser divided conflicts into several parts, there are realistic, non- realistic, in- group and out- group conflicts. He argues that social conflict not only viewed from the negative side. This research focuses on social conflicts that occur the Japanese student environment then will analyze more deeply the social conflicts experienced by the main character also will look for the factors that occurs the conflicts.  Thie aim of this studies to explains and describing (1) realistic and non- realistic conflicts that occur (2) in-group and out-group conflicts that occur (3) functions of social conflicts. This study used content analysis of qualitative research methods with literary sociology approach. For data collecting technique this study used note- taking technique. The result of this research is (1) the occurrence of realistic conflicts due to a sense of disapproval of a demand (2) the occurrence of non- realistic conflicts due to the need to relieve tensions (3) the occurrence of in-group conflicts because those involved in the conflicts are between member in the same groups (4) the occurrence of out-group conflicts because those involved in the conflicts are between different groups.